Liver injury associated with the severity of COVID-19: A meta-analysis - Yang, Ruiqi; Feng, Jihua; Wan, Huan; Zeng, Xiaona; Ji, Pan; Zhang, Jianfeng (Frontiers in Public Health, 2023)
Background The current 2019 novel coronavirus disease (COVID-19) pandemic is a major threat to global health. It is currently uncertain whether and how liver injury affects the severity of COVID-19. Therefore, we conducted a meta-analysis to determine the association between liver injury and the severity of COVID-19. Methods A systematic search of the PubMed, Embase, and Cochrane Library databases from inception to August 12, 2022, was performed to analyse the reported liver chemistry data for patients diagnosed with COVID-19. The pooled odds ratio (OR), weighted mean difference (WMD) and 95% confidence interval (95% CI) were assessed using a random-effects model. Furthermore, publication bias and sensitivity were analysed. Results Forty-six studies with 28663 patients were included. The pooled WMDs of alanine aminotransferase [(WMD=12.87 U/L, 95% CI:10.52 to 15.23, I2=99.2%], aspartate aminotransferase [(WMD= 13.98 U/L, 95% CI:12.13 to 15.83, I2=98.2%], gamma-glutamyl transpeptidase [(WMD=20.67 U/L, 95% CI:14.24 to 27.10, I2=98.8%], total bilirubin [(WMD=2.98 µmol/L, 95% CI:1.98 to 3.99, I2=99.4%], and prothrombin time [(WMD= 0.84 s, 95% CI:0.46 to 1.23, I2=99.4%] were significantly higher and that of albumin was lower [(WMD=-4.52 g/L, 95% CI:-6.28 to -2.75, I2=99.9%] in severe cases. Moreover, the pooled OR of mortality was higher in patients with liver injury (OR=2.72, 95% CI:1.18 to 6.27, I2=71.6%). Conclusions Hepatocellular injury, liver metabolic, and synthetic function abnormality were observed in severe COVID-19. From a clinical perspective, liver injury has potential as a prognostic biomarker for screening severely affected patients at early disease stages.